2001
DOI: 10.2527/2001.793722x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of betaine on growth, carcass characteristics, pork quality, and plasma metabolites of finishing pigs.

Abstract: An experiment was conducted to determine the effect of dietary betaine (0, 0.125, 0.250, or 0.500%) on growth, carcass traits, pork quality, plasma metabolites, and tissue betaine concentrations of cross-bred finishing pigs. Four replications of three pigs (two barrows and one gilt) each were used for each treatment. The basal diet contained 0.85 (69 to 88 kg BW) or 0.65% Lys (88 to 115 kg BW). Overall ADG and gain:feed were not affected (P > 0.10) by betaine, but overall ADFI was decreased (quadratic, P < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
91
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 0 publications
17
91
8
Order By: Relevance
“…Although increased total cholesterol (Matthews et al, 2001;Martins et al, 2010) and decreased HDL/total cholesterol (Martins et al, 2010) have been reported in pigs fed betaine, other authors reported no betaine effect on cholesterol, plasma NEFA or TG (Matthews et al, 1998;Øverland et al, 1999). We found decreased HDL/total cholesterol in betaine pigs, but no significant effects in total cholesterol or fractions.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Although increased total cholesterol (Matthews et al, 2001;Martins et al, 2010) and decreased HDL/total cholesterol (Martins et al, 2010) have been reported in pigs fed betaine, other authors reported no betaine effect on cholesterol, plasma NEFA or TG (Matthews et al, 1998;Øverland et al, 1999). We found decreased HDL/total cholesterol in betaine pigs, but no significant effects in total cholesterol or fractions.…”
Section: Discussioncontrasting
confidence: 56%
“…Most studies with betaine in pigs focus on the effect of betaine on growth performance, carcass characteristics and pork quality. Several reports have indicated that betaine could decrease carcass fat deposition and increase carcass lean in pigs (Matthews et al, 2001;Ferná ndez-Fígares et al, 2002), -E-mail: ifigares@eez.csic.es especially under restricted energy intake (Suster et al, 2004) conditions. In contrast, CLA is a collective name that refers to a mixture of positional and geometric conjugated isomers of linoleic acid.…”
Section: Introductionmentioning
confidence: 99%
“…When male andf emale pigs have been compared directly, conflicting results have been previously obtained with respect to ability of betaine to alter growth and lipid metabolism (Lawrence et al, 2002). The previously noted decrease in voluntary feed intake has been reported in betaine growth trials with females alone or with groups of mixed sexes (Matthews et al, 1998(Matthews et al, , 2001a. The Finnish study used mixed genders (females and castrated males), but they did not report their data by gender (Siljander-Rasi et al, 2003).…”
Section: Discussionmentioning
confidence: 76%
“…The pigs were restrictively fed (80% ad libitum) and housed in a very confined space (metabolism crates). In trials in which pigs are given ad libitum access to feed, a tendency towards a reduction in voluntary feed intake has been reported, accompanied by no change in overall growth (Matthews et al, 1998(Matthews et al, , 2001a). In the current experiment, where feed intake was strictly controlled and limited to 80% of expected ad libitum intake, the improvement in feed:gain ratio resulted in the overall observed increase in growth rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation